What happens during early outpatient palliative care consultations for persons with newly diagnosed advanced cancer? A qualitative analysis of provider documentation. (January 2018) - Bagcivan, Gulcan; Dionne-Odom, J Nicholas; Frost, Jennifer; Plunkett, Margaret; Stephens, Lisa A; Bishop, Peggy; Taylor, Richard A; Li, Zhongze; Tucker, Rodney; Bakitas, Marie
Background: Early outpatient palliative care consultations are recommended by clinical oncology guidelines globally. Despite these recommendations, it is unclear which components should be included in these encounters. Aim: Describe the evaluation and treatment recommendations made in early outpatient palliative care consultations. Design: Outpatient palliative care consultation chart notes were qualitatively coded and frequencies tabulated. Setting/participants: Outpatient palliative care consultations were automatically triggered as part of an early versus delayed randomized controlled trial (November 2010 to April 2013) for patients newly diagnosed with advanced cancer living in the rural Northeastern US. Results: In all, 142 patients (early = 70; delayed = 72) had outpatient palliative care consultations. The top areas addressed in these consultations were general evaluations—marital/partner status (81.7%), spirituality/emotional well-being (80.3%), and caregiver/family support (79.6%); symptoms—mood (81.7%), pain (73.9%), and cognitive/mental status (68.3%); general treatment recommendations—counseling (39.4%), maintaining current medications (34.5%), and initiating new medication (23.9%); and symptom-specific treatment recommendations—pain (22.5%), constipation (12.7%), depression (12.0%), advanced directive completion (43.0%), identifying a surrogate (21.8%), and discussing illness trajectory (21.1%). Compared to the early group, providers were more likely to evaluate general pain ( p = 0.035) and hospice awareness ( p = 0.005) and discuss/recommend hospice ( p = 0.002) in delayed group participants. Conclusion: Outpatient palliative care consultations for newly diagnosed advanced cancer patients can address patients' needs and provide recommendations on issues that might not otherwise be addressed early in the disease course. Future prospective studies should ascertain the value of early outpatient palliative care consultations that are automatically triggered based on diagnosis or documented symptom indicators versus reliance on oncologist referral.